3D hole-transporting materials based on coplanar quinolizino acridine for highly efficient perovskite solar cells. Issue 11 (4th October 2017) - Zhang, Mingdao; Wang, Gang; Zhao, Danxia; Huang, Chengyan; Cao, Hui; Chen, Mindong
Abstract : A new concept of HTMs for PSCs: a 3D structure with a core of coplanar quinolizino is firstly put forward and demonstrated to be highly effective, and it is derived from the conventional concept of 2D triphenylamine HTM. Abstract : Over the past five years, perovskite solar cells (PSCs) have gained intense worldwide attention in the photovoltaic community due to their low cost and high power conversion efficiencies (PCEs). One of the most significant issues in achieving high PCEs of PSCs is the development of suitable low-cost hole-transporting materials (HTMs). Here, we put forward a new concept of HTMs for PSCs: a 3D structure with a core of coplanar quinolizino acridine, derived from the conventional concept of 2D triphenylamine HTMs. A cheaper Ag nanolayer was utilized to replace Au as the counter electrodes, and the title HTM TDT-OMeTAD was synthesized via an easy four-step synthesis (total yield: 61%) to achieve the low cost and convenient manufacture of PSCs. Compared with the conventional 2D triphenylamine HTM, TTPA-OMeTPA, PSC devices based on the 3D HTM TDT-OMeTPA showed a significant improvement in PCE from 10.8% to 16.4%, even outperforming Spiro-OMeTAD (14.8%). TDT-OMeTAD's highest PCE mainly results from it having the highest open-circuit voltage ( V oc ) of 1.01 V in this work, which is proven to be due to the higher hole mobility, matching energy levels, higher hydrophobicity and the smaller dark current. Moreover, an incident photon–current conversion efficiency (IPCE) test and time-resolved photoluminescence (TRPL) have been carried out to observe the better hole injecting efficiency and photoelectric conversion capability of TDT-OMeTPA based PSCs than Spiro-OMeTAD. The TDT-OMeTPA based PSCs exhibited >75% reproducibility (PCE > 15%) and retained 93.2% of the initial PCE after >500 hours.